(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article analyzes the novel "The Sun does not darken", one of the famous works of Oybek Musa Toshmuhammad ugli, the favorite writer of our people. The novel is about the war, in which the author vividly describes the events he witnessed. Through the work, the writer once again demonstrated his observation, artistic skill and vocabulary. In the article, exactly those things are described.